Mulberry extract to modULate Blood glucosE Responses in noRmoglYcaemic adults (MULBERRY): study protocol for a randomised controlled trial. Issue 1 (December 2015) - Lown, Mark; Fuller, Richard; Lightowler, Helen; Fraser, Ann; Gallagher, Andrew; Stuart, Beth; Byrne, Christopher; Lewith, George
Abstract Background Worldwide sugar consumption has tripled during the last fifty years. High sugar intake is associated with weight gain and increased incidence of diabetes and has been linked with increased cardiovascular mortality. Reducing the health impact of dietary sugar and poor quality carbohydrate intake is a public health priority. IminoNorm®, a proprietary mulberry leaf extract (ME), may reduce blood glucose responses following dietary sugar and carbohydrate intake by reducing absorption of glucose from the gut. Previous research has shown that ME can reduce blood glucose and improve insulin responses in healthy subjects and also in subjects with raised fasting blood glucose levels. Mulberry leaf has an excellent safety profile. This pilot study will test a novel, safe, water soluble product in normoglycaemic adults in the UK to determine if it can reduce glucose absorption without increasing plasma insulin concentration. Methods/design The trial will be a double-blind, individually randomised, four-arm single-dose crossover design to test the effect of three doses of ME in order to determine efficacy, dose response relationship and gastrointestinal side effects with respect to placebo. A total of 40 subjects will participate in this study and attend for four visits receiving each of the four interventions in random order. Discussion We aim to test the evidence that mulberry leaf extract can reduce blood glucose without a disproportionate increase in blood insulin responses in healthy individuals in a high-quality research study based in the UK. It is hoped that this will lead to further randomised controlled trials and an effective dietary supplement to lower blood glucose concentrations. Trial registration ISRCTN:ISRCTN14597438 (21 April 2015)